Ou Testamentiese literatuur uit die Noordryk (Israel) - Die neerslag van noordelike tradisies in die Ou Testament - W.S. Boshoff (Verbum et Ecclesia, 2000)
Old Testament literature from the Northern Kingdom (Israel): The presence of northern traditions in the Old Testament The literature originating from the Northern Kingdom of Israel conveys an important message in terms of the theological themes in the Old Testament. Several of the earliest prophetic characters, such as Elijah, Elisha, Amos and Hosea, were all active in the Northern Kingdom. The political and religious situation of the Northern Kingdom created the context for these prophets, and other authors who shaped the thinking about God in old Israel. There writings can be found in the Pentateuch, Deuteronomy and the Deuteronomistic History, as well as in the books of Amos, Hosea and Deutero-Micha.